The Zheng Family and the Dutch in the Malay Archipelago: Competition and Conflict in the 17th Century - Ku, Boon Dar (Penerbit Universiti Sultan Zainal Abidin, 2018)
This paper attempts to examine the development of the Zheng family’s trading activities in the Malay Archipelago, especially during the time of Zheng Chenggong, when the family had to compete with the Dutch in the Straits of Malacca. For this purpose, the qualitative analytical approaches are employed with reference to the primary sources of the Western and Chinese travellers during the 17th century, namely, Willem Ysbrandsz Bontekoe and George Hughes, apart from the gazettes annotated by Li Jinming and Liao Da Ke. In addition, secondary sources, such as the books, monographs, articles and journals written by some distinguished scholars in the field of international maritime research have been studied. The works of Patrizia Carioti, Leonard Blusse, Meilink-Roelofsz and Xing Hang, among others, have also been investigated for their critical views and arguments. In sum, this study aims to show that trade conflicts and competition between the Zheng family and the Dutch in the 17th century have impacted particularly the Chinese traders in the Malay Archipelago. This is because both of these powers are seen trying to assume the role which had hitherto been played by these Chinese merchants as a strong competitor in the marine trade in the east and southeast of the Malay Archipelago. In this regard, discussions on this topic would contribute to a better understanding of the big powers competing in the region to dominate the Straits of Malacca. Additionally, this study sets to prove that private trading activities in the Malay Archipelago which flourished during the 17th century was built and developed by the Zheng family from Taiwan and not merely attributed to the Chinese traders from China.